Roles of the ubiquitin proteasome system in the effects of drugs of abuse - Massaly, Nicolas; Francès, Bernard; Moulédous, Lionel (Frontiers in Molecular Neuroscience, 2015)
Because of its ability to regulate the abundance of selected proteins the ubiquitin proteasome system (UPS) plays an important role in neuronal and synaptic plasticity. As a result various stages of learning and memory depend on UPS activity. Drug addiction, another phenomenon that relies on neuroplasticity, shares molecular substrates with memory processes. However the necessity of proteasome-dependent protein degradation for the development of addiction has been poorly studied. Here we first review evidences from the literature that drugs of abuse regulate the expression and activity of the UPS system in the brain. We then provide a list of proteins which have been shown to be targeted to the proteasome following drug treatment and could thus be involved in neuronal adaptations underlying behaviors associated with drug use and abuse. Finally we describe the few studies that addressed the need for UPS-dependent protein degradation in animal models of addiction-related behaviors.